The immersive turn: hype and hope in the emergence of virtual reality as a nonfiction platform. Issue 2 (4th May 2018) - Rose, Mandy
ABSTRACT: This article responds to the recent wave of experimentation with Virtual Reality (VR) as a nonfiction platform. Amidst daily announcements of new VR documentary initiatives, and at times giddy claims about the potential of this new medium, I consider how a media technology expected to enter the mainstream as a games platform became a magnet for nonfiction producers. VR is not a new medium, and has been the subject of a substantial body of research across arts and science. This research is also the site of claims for the pro-social potential of VR, which provide a significant context for its adoption for nonfiction. Less attention has been given to ethical risks posed by VR, which I highlight, and which I suggest require attention within documentary practice. The article concludes with a discussion of the symbiotic relationship between technology and content development in this arena. All these factors have come together at the intersection of VR and nonfiction to produce a heady mix of commercial excitement (hype) and techno-utopianism (hope) which this article highlights and analyses.